Administration in Improving Church Stewardship - Iin Nur Indrayani Sihombing (Journal of Social Research, 2023)
The need for administration in efficient church stewardship is discussed, as is a good model of church administration. To improve church stewardship, the journal uses the literature study method to discuss effective church administration models that can adapt to the changing needs and goals of the church, consider the internal and external environment of the church, and provide clear direction to all members. The journal also explains why administration is essential to effective church stewardship. Stewardship in the church includes the maintenance of a wide variety of ministries, including services devoted to worship, spiritual formation, and social action. Church stewardship benefits from a well-organized administration in terms of managing resources, planning events, and minimizing waste. Communication, leadership, and member participation are just a few examples of what can have a positive or negative impact on the efficiency of church administration and stewardship. The authors also offer a number of suggestions for improving the efficiency of church administration and stewardship, including developing better administrative and leadership capabilities, improving communication channels, and encouraging greater participation from members. In short, the journals in this publication explain why efficient church management is so important. Good stewardship in religious institutions.